2002
DOI: 10.1159/000058000
|View full text |Cite
|
Sign up to set email alerts
|

Rat Monoclonal Anti-Murine IgE Antibody Removes IgE Molecules Already Bound to Mast Cells or Basophilic Leukemia Cells, Resulting in the Inhibition of Systemic Anaphylaxis and Passive Cutaneous Anaphylaxis

Abstract: IgE plays a central role in allergic reactions. Some anti-IgE antibodies (HMK-12, 6HD5) inhibit the binding of IgE to the FcΕRI of mast cells/basophilic leukemia cells (PT-18, RBL/2H3), but less inhibition is seen with the anti-allotypic JKS-6 and the anti-idiotypic Eb-1. Anti-IgE HMK-12 can detach bound IgE molecules from the FcΕRI. When mast cells or basophils were incubated with monoclonal anti-DNP-IgE SPE-7, washed and treated with anti-IgE HMK-12, anti-IgE/IgE complexes were found in the supernatant. Simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…However, deletion of the Cε2 domain from the IgE H chain constant region increased the rate of dissociation of IgE from the receptor, which suggests that the IgE Cε2 domain plays a pivotal role in stabilizing the interaction of IgE with FcεRIα 36 . These findings support our previous observations that indicate that some anti-IgE antibodies, including 6HD5, can remove an IgE molecule already bound to FcεRIα on the surface of mast cells or basophilic leukemia cells and inhibit IgE-mediated systemic or local anaphylactic reactions 33 , 37 .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, deletion of the Cε2 domain from the IgE H chain constant region increased the rate of dissociation of IgE from the receptor, which suggests that the IgE Cε2 domain plays a pivotal role in stabilizing the interaction of IgE with FcεRIα 36 . These findings support our previous observations that indicate that some anti-IgE antibodies, including 6HD5, can remove an IgE molecule already bound to FcεRIα on the surface of mast cells or basophilic leukemia cells and inhibit IgE-mediated systemic or local anaphylactic reactions 33 , 37 .…”
Section: Resultssupporting
confidence: 92%
“…These antibodies are thought to recognize the binding sites of IgE for FcεRIα. We have previously shown that the anti-IgE antibody HMK-12 also inhibits the binding of IgE to the IgE-FcεRIα complex 33 . By contrast, Fab-6HD5 appears to suppress the release of chemical mediators after IgE antigen-mediated crosslinking of surface FcεRIα, which indicates that this antibody is not a competitive inhibitor of the IgE-FcεRIα interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IgG is involved in anaphylactic shock or even death induced by antigens of parasites alongside IgE [ 14 , 21 ]. IgG accounts for about 75–80% of all immunoglobulins in the serum, and consists of 4 subtypes, IgG1, IgG2, IgG3, and IgG4 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies SPE-7 IgE (anti-DNP murine IgE antibody) and SPE-7 IgE F(ab')2 were purchased from Sigma-Aldrich Co. LLC (USA) and Immuno-Biological Laboratories Co., Ltd. (Gunma, JAPAN), respectively. The rat monoclonal antibody HMK-12 (speci c for murine IgE) was used as described previously 30,37 . Rat IgG anti-murine κ antibodies and HRP-labelled goat anti-rat IgG were purchased from BioLegend (CA, USA) and Jackson ImmunoResearch (PA, USA), respectively.…”
Section: Animals and Cellsmentioning
confidence: 99%